Question and Answers Forum

All Questions      Topic List

Others Questions

Previous in All Question      Next in All Question      

Previous in Others      Next in Others      

Question Number 101231 by 175 last updated on 01/Jul/20

Commented by Dwaipayan Shikari last updated on 01/Jul/20

(1/n).(π/6)lim_(n→∞) ((2^(1/n) −1)/(1/n)) Σ_(r=0) ^n (2^(r/n) cos(2^(r/n) (π/6)))  (π/6) log2 ∫_0 ^1 2^x cos(2^x (π/6))dx  ∫_0 ^1 cos(2^x (π/6))2^x (π/6)log2dx   ∫_(π/6) ^(π/3) cost dt =[sint]_(π/6) ^(π/3) =(((√3)−1)/2)  {suppose 2^x (π/6)=t}

$$\frac{\mathrm{1}}{{n}}.\frac{\pi}{\mathrm{6}}\underset{{n}\rightarrow\infty} {\mathrm{lim}}\frac{\mathrm{2}^{\frac{\mathrm{1}}{{n}}} −\mathrm{1}}{\frac{\mathrm{1}}{{n}}}\:\underset{{r}=\mathrm{0}} {\overset{{n}} {\sum}}\left(\mathrm{2}^{\frac{{r}}{{n}}} {cos}\left(\mathrm{2}^{\frac{{r}}{{n}}} \frac{\pi}{\mathrm{6}}\right)\right) \\ $$$$\frac{\pi}{\mathrm{6}}\:{log}\mathrm{2}\:\int_{\mathrm{0}} ^{\mathrm{1}} \mathrm{2}^{{x}} {cos}\left(\mathrm{2}^{{x}} \frac{\pi}{\mathrm{6}}\right){dx} \\ $$$$\int_{\mathrm{0}} ^{\mathrm{1}} {cos}\left(\mathrm{2}^{{x}} \frac{\pi}{\mathrm{6}}\right)\mathrm{2}^{{x}} \frac{\pi}{\mathrm{6}}{log}\mathrm{2}{dx} \\ $$$$\:\int_{\frac{\pi}{\mathrm{6}}} ^{\frac{\pi}{\mathrm{3}}} {cost}\:{dt}\:=\left[{sint}\right]_{\frac{\pi}{\mathrm{6}}} ^{\frac{\pi}{\mathrm{3}}} =\frac{\sqrt{\mathrm{3}}−\mathrm{1}}{\mathrm{2}} \\ $$$$\left\{{suppose}\:\mathrm{2}^{{x}} \frac{\pi}{\mathrm{6}}={t}\right\} \\ $$

Answered by smridha last updated on 01/Jul/20

(𝛑/6)lim_(n→∞) ((2^(1/n) −1)/(1/n)).[lim_(n→∞) (1/n).Σ_(r=0) ^n 2^(r/n) .cos(2^(r/n) .(𝛑/6))]  =(𝛑/6).ln(2).∫_(0 ) ^1 2^x .cos(2^x .(𝛑/6))dx  =(𝛑/6).ln2.(6/(𝛑.ln(2)))∫_0 ^1 d[sin(2^x .(𝛑/6))]  =1.[sin(2^x .(𝛑/6))]_0 ^1 =[sin(𝛑/3)−sin(𝛑/6)]      =((√3)/2)−(1/2)=(((√3)−1)/2).

$$\frac{\boldsymbol{\pi}}{\mathrm{6}}\underset{\boldsymbol{{n}}\rightarrow\infty} {\mathrm{lim}}\frac{\mathrm{2}^{\frac{\mathrm{1}}{\boldsymbol{{n}}}} −\mathrm{1}}{\frac{\mathrm{1}}{\boldsymbol{{n}}}}.\left[\underset{\boldsymbol{{n}}\rightarrow\infty} {\mathrm{lim}}\frac{\mathrm{1}}{\boldsymbol{{n}}}.\underset{\boldsymbol{{r}}=\mathrm{0}} {\overset{\boldsymbol{{n}}} {\sum}}\mathrm{2}^{\frac{\boldsymbol{{r}}}{\boldsymbol{{n}}}} .\boldsymbol{{cos}}\left(\mathrm{2}^{\frac{\boldsymbol{{r}}}{\boldsymbol{{n}}}} .\frac{\boldsymbol{\pi}}{\mathrm{6}}\right)\right] \\ $$$$=\frac{\boldsymbol{\pi}}{\mathrm{6}}.\boldsymbol{{ln}}\left(\mathrm{2}\right).\int_{\mathrm{0}\:} ^{\mathrm{1}} \mathrm{2}^{\boldsymbol{{x}}} .\boldsymbol{{cos}}\left(\mathrm{2}^{\boldsymbol{{x}}} .\frac{\boldsymbol{\pi}}{\mathrm{6}}\right)\boldsymbol{{dx}} \\ $$$$=\frac{\boldsymbol{\pi}}{\mathrm{6}}.\boldsymbol{{ln}}\mathrm{2}.\frac{\mathrm{6}}{\boldsymbol{\pi}.\boldsymbol{{ln}}\left(\mathrm{2}\right)}\int_{\mathrm{0}} ^{\mathrm{1}} \boldsymbol{{d}}\left[\boldsymbol{{sin}}\left(\mathrm{2}^{\boldsymbol{{x}}} .\frac{\boldsymbol{\pi}}{\mathrm{6}}\right)\right] \\ $$$$=\mathrm{1}.\left[\boldsymbol{{sin}}\left(\mathrm{2}^{\boldsymbol{{x}}} .\frac{\boldsymbol{\pi}}{\mathrm{6}}\right)\right]_{\mathrm{0}} ^{\mathrm{1}} =\left[\boldsymbol{{sin}}\frac{\boldsymbol{\pi}}{\mathrm{3}}−\boldsymbol{{sin}}\frac{\boldsymbol{\pi}}{\mathrm{6}}\right] \\ $$$$\:\:\:\:=\frac{\sqrt{\mathrm{3}}}{\mathrm{2}}−\frac{\mathrm{1}}{\mathrm{2}}=\frac{\sqrt{\mathrm{3}}−\mathrm{1}}{\mathrm{2}}. \\ $$

Commented by 175 last updated on 01/Jul/20

thanx

Commented by smridha last updated on 01/Jul/20

welcome...but careful there is a group ��������

Terms of Service

Privacy Policy

Contact: info@tinkutara.com